Automation of the cytokinesis-block micronucleus cytome assay by laser scanning cytometry and its potential application in radiation biodosimetry - Maxime François; Kevin Hochstenbach; Wayne Leifert; Michael Felix Fenech (BioTechniques, 2014)
Here we describe the adaptation of laser scanning cytometry (LSC) to measure micronuclei (MN) automatically in lymphocytes. MN frequencies were determined in irradiated human lymphocytes using the cytokinesis-block technique, and the results from LSC were compared with visual scoring results obtained from slides of cells stained using Fast Green and 4′,6-diamidino-2-phenylindole (DAPI). This fluorescent approach allowed clear identification of binucleated cells and detection of MN. The dose responses measured visually and by LSC showed similar trends and correlated positively (r = 0.9689; P < 0.0001). High-content analysis was developed to further automatically score MN within mono-, tri- and tetra-nucleated cells and to determine the nuclear division index and nuclear circularity values. The high-throughput nature of LSC can provide unique advantages in future DNA damage diagnostics in experimental and epidemiological studies. Importantly, it allows for co-detection of other biomarkers of interest within a single lymphocyte, and further development of this capability is anticipated.